Prussian blue stepped cubic framework / polypyrrole composite electrode material and preparation method and application thereof

By combining the cube Prussian blue frame with an inner recessed step structure with polypyrrole to form a multi-dimensional conductive network, the problems of poor conductivity and insufficient structural stability of the existing capacitive deionized electrode materials are solved, and efficient desalination performance and good cycle stability are achieved.

CN119551771AActive Publication Date: 2025-03-04HUNAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411502895.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-04
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing capacitor deionized electrode materials have defects such as poor conductivity, small contact area of ​​electrolyte, few active sites, long Na+ diffusion path, and poor structural stability, resulting in slow ion diffusion rate, smaller than capacitance, poor cycle stability, low charging efficiency, and high energy consumption.

Method used

A cube Prussian blue frame with an inner depression ladder structure is combined with polypyrrole, and a multi-dimensional conductive network is formed through the adhesion and growth of granular and dendritic polypyrroles and the series connection to improve the conductivity and mechanical stability of the electrodes.

Benefits of technology

The composite electrode material with large contact area, many active sites, suitable Na+ diffusion path, good conductivity and stable structure is achieved, which significantly improves the desalination performance of the electrode, has faster ion diffusion rate, larger specific capacitance, better cycling stability and higher charging efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551771A_ABST
    Figure CN119551771A_ABST
Patent Text Reader

Abstract

The invention discloses a Prussian blue stepped cubic framework / polypyrrole composite electrode material and a preparation method and application thereof.The composite electrode material comprises a cubic Prussian blue framework, granular polypyrrole and dendritic polypyrrole, and the granular polypyrrole adheres to and grows on the surfaces of the Prussian blue cubic framework and the dendritic polypyrrole; the dendritic polypyrrole is connected between the cubic Prussian blue frameworks. In the invention, under the combined action of a cubic Prussian blue framework and polypyrrole, a multi-dimensional structure can be formed by means of adhesion growth, series connection and the like, so that the composite material shows very excellent oxidation-reduction activity and conductivity; the composite electrode has the advantages of large electrolyte contact area, multiple active sites, proper Na < + > diffusion path, good conductivity, good structural stability and the like, can remarkably promote the desalination performance of the electrode when being used for preparing the capacitive deionization electrode, can promote the wide application of the electrode in the field of seawater desalination, and is high in use value and good in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of desalination treatment of salt water, and relates to a Prussian blue stepped cubic framework / polypyrrole composite electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid population growth, rapid industrialization and increasing climate change, the supply of clean fresh water has become a particularly prominent issue. In particular, in arid and semi-arid regions, the lack of fresh water resources poses a severe challenge to the daily lives and economic development of local residents. Therefore, the development of new fresh water acquisition technologies, especially seawater desalination technologies, has become a global urgent need.

[0003] As a desalination technology, capacitive deionization (CDI) is considered to be one of the effective ways to solve the problem of fresh water shortage due to its high efficiency, environmental protection and low energy consumption. CDI technology is a method of removing ions from water using electrochemical principles. It achieves water desalination by applying a potential difference between electrodes and using electrochemical principles to adsorb ions in the solution. It can be seen that the desalination efficiency of CDI technology and the performance of electrode materials are key factors for its commercial application and are also the focus of current research.

[0004] In the research and application of CDI technology, the development of capacitive deionization electrodes is one of the key challenges. Although traditional carbon electrodes are low in cost, their adsorption capacity is limited. In order to improve the performance of CDI, researchers are exploring Faradaic electrode materials based on redox processes, which exhibit higher ion storage capacity due to their redox reactions. For example, by preparing Prussian blue and its analogs (PBAs) on the electrode surface, selective adsorption of specific ions can be achieved through Faradaic reactions. However, PBAs prepared by existing preparation methods still have defects such as poor conductivity, making it difficult to achieve efficient adsorption of target ions in water bodies, and the contact area between PBAs electrodes and electrolytes reported so far is still low, and are plagued by various shortcomings, such as poor stability due to lattice expansion, Na + The long diffusion path leads to slow diffusion kinetics, easy aggregation and stacking, and insufficient utilization of active sites. In order to improve the conductivity of PBAs, some researchers have proposed introducing conductive polymers on the surface of PBAs, but the introduction of conductive polymers easily blocks the pores of PBAs, resulting in a smaller specific surface area of ​​the prepared composite material and shielding of active sites. In addition, the capacitive deionization electrode prepared from the above composite material also has shortcomings such as slow ion diffusion rate, small specific capacitance, poor cycle stability, low charging efficiency, and high energy consumption. Ultimately, it is difficult to use capacitive deionization electrodes to achieve higher desalination rates and better desalination effects.

[0005] Therefore, an electrolyte with large contact area, many active sites, and Na + Composite electrode materials with suitable diffusion paths, good conductivity and stable structure are of great significance for improving the electrical properties of capacitive deionization electrodes and promoting their widespread application in the field of seawater desalination. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide an electrolyte with a large contact area, a large number of active sites, and a Na + A Prussian blue stepped cubic framework / polypyrrole composite electrode material with suitable diffusion path, good conductivity and stable structure, and a preparation method and application thereof.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A Prussian blue stepped cubic framework / polypyrrole composite electrode material comprises a cubic Prussian blue framework with an inner concave stepped structure and polypyrrole, wherein the polypyrrole comprises granular polypyrrole and dendritic polypyrrole; the granular polypyrrole is attached and grown on the surface of the Prussian blue cubic framework and the dendritic polypyrrole, and the dendritic polypyrrole is connected between the cubic Prussian blue framework.

[0009] The above-mentioned Prussian blue step cubic framework / polypyrrole composite electrode material is further improved in that the mass ratio of the cubic Prussian blue framework to polypyrrole is 0.8-1.5:1.

[0010] The above-mentioned Prussian blue stepped cubic framework / polypyrrole composite electrode material is further improved in that the mass ratio of the cubic Prussian blue framework to polypyrrole is 1:1.

[0011] As a general technical concept, the present invention also provides a method for preparing the above-mentioned Prussian blue step cubic framework / polypyrrole composite electrode material, comprising the following steps:

[0012] (1) preparing a cubic Prussian blue framework with an inner concave step structure;

[0013] (2) mixing the cubic Prussian blue framework with an inner concave step structure obtained in step (1), methyl orange and water, ultrasonicating and stirring to obtain a solution A; the amount of methyl orange used is more than 120 mg;

[0014] (3) adding pyrrole to the solution A obtained in step (2), stirring, and obtaining a solution B; the amount of pyrrole used is more than 280 μL;

[0015] (4) adding the solution B obtained in step (3) to the ferric iron salt solution, mixing and reacting in an ice bath, centrifuging, and washing to obtain a Prussian blue step cubic framework / polypyrrole composite electrode material; the amount of the ferric iron salt solution used is above 18.4 mL.

[0016] The above preparation method is further improved, in step (1), the preparation method of the cubic Prussian blue framework with an inner concave step structure comprises the following steps:

[0017] (1.1) Mix benzoic acid and ethanol to prepare solution C;

[0018] (1.2) Solution C and solution D are mixed to perform a hot solvent reaction, centrifuged, washed, and dried to obtain a cubic Prussian blue framework with an inner concave step structure; the solution D is prepared by mixing Na4Fe(CN)6·10H2O with water.

[0019] The above preparation method is further improved, in step (1.1), the ratio of benzoic acid to ethanol is 1mmoL:4m.

[0020] The above preparation method is further improved, in step (1.2), the volume ratio of solution C to solution D is 4:3; the ratio of Na4Fe(CN)6·10H2O to water is 1.4mmoL:15mL; the hot solvent reaction is carried out at a temperature of 120°C; the hot solvent reaction time is 6h; the centrifugal speed is 6500r / min; the washing is to wash the centrifuged product with ethanol and deionized water in sequence; the number of washings is 3 times; the drying is carried out under vacuum conditions; the drying temperature is 60°C; and the drying time is 12h.

[0021] The above preparation method is further improved, in step (2), the mass ratio of the cubic Prussian blue framework to methyl orange is 1:1; the ratio of methyl orange to water is 3 mg:4 mL; the ultrasonic time is 15 min; the stirring is carried out at a rotation speed of 400 r / min; and the stirring time is 12 min.

[0022] The above preparation method is further improved, in step (3), the volume ratio of pyrrole to solution A is 0.7:40; the stirring is carried out at a rotation speed of 400 r / min; and the stirring time is 15 min.

[0023] The above preparation method is further improved, in step (4), the trivalent iron salt solution is a ferric chloride solution; the ferric chloride solution is prepared by the following method: FeCl3·6H2O is added to ultrapure water, and stirred for 15 minutes at a rotation speed of 600r / min~800r / min to obtain a ferric chloride solution; the ratio of FeCl3·6H2O to ultrapure water is 1.08g:18.4mL; the reaction temperature is 0°C; the reaction time is 24h; the reaction is carried out at a rotation speed of 600r / min~800r / min; the centrifugal speed is 6500r / min; the single centrifugal time is 5min; the washing is to wash the centrifuged product with ethanol and deionized water in sequence; the number of washing times is 3 times; the drying temperature is 60°C; the drying time is 24h.

[0024] As a general technical concept, the present invention also provides a capacitor deionization electrode, which is prepared from the above-mentioned Prussian blue step cubic framework / polypyrrole composite electrode material or the Prussian blue step cubic framework / polypyrrole composite electrode material prepared by the above-mentioned preparation method.

[0025] The above-mentioned capacitor deionization electrode is further improved, and the capacitor deionization electrode is prepared from a Prussian blue stepped cubic framework / polypyrrole composite electrode material, conductive carbon black and a binder, comprising the following steps: mixing the Prussian blue stepped cubic framework / polypyrrole composite electrode material, conductive carbon black and a binder, adding a solvent to form a colloid; coating the colloid on a conductive carrier, and drying to obtain a capacitor deionization electrode.

[0026] The above-mentioned capacitor deionization electrode is further improved, wherein the mass ratio of the Prussian blue stepped cubic framework / polypyrrole composite electrode material, conductive carbon black and binder is 8-9:0.8-1:0.8-1; the binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol and polypropylene; and the solvent is N-methylpyrrolidone.

[0027] As a general technical concept, the present invention also provides an application of the above-mentioned capacitive deionization electrode in solution desalination.

[0028] In the present invention, when the capacitor deionization electrode is used for solution desalination, the following steps are included: a capacitor deionization device is constructed with the capacitor deionization electrode as a cathode and an activated carbon electrode as an anode to desalinate a saline solution; the saline solution is brackish water or seawater.

[0029] The innovation of the present invention is:

[0030] (1) The existing capacitive deionization electrodes have poor conductivity, small electrolyte contact area, few active sites, and Na+ The invention provides a Prussian blue step cubic framework / polypyrrole composite electrode material, which includes a cubic Prussian blue framework with an inner concave step structure and polypyrrole, wherein the polypyrrole includes granular polypyrrole and dendritic polypyrrole, wherein the granular polypyrrole is attached and grown on the surface of the Prussian blue cubic framework and the dendritic polypyrrole, and the dendritic polypyrrole is connected between the cubic Prussian blue framework. Compared with conventional Prussian blue and its analogs, the cubic Prussian blue framework used in the present invention has an inner concave step structure, which has a high density of surface steps, and these steps can provide more active sites for the adsorption of ions, and have good redox performance and sodium storage capacity. At the same time, the Prussian blue crystals with abundant steps and concave surfaces help to increase the contact area between the electrode and the solution, thereby improving the adsorption efficiency of ions. On this basis, granular polypyrrole is attached and grown on the surface of the Prussian blue cubic framework, and polypyrrole is combined with the Prussian blue cubic ladder structure in an attached growth manner to form a multidimensional conductive network. This network can not only improve the conductivity of the electrode, but also increase the mechanical stability of the electrode, so that the electrode can maintain stable performance during long-term desalination. More importantly, the dendritic polypyrrole is connected between the cubic Prussian blue frameworks, so that multiple Prussian blue cubic ladder structures are connected through the dendritic polypyrrole, forming a multidimensional structure similar to a "series circuit". This design enables each Prussian blue unit to independently adsorb ions under the action of an electric field, thereby improving the overall desalination efficiency. In addition, compared with polypyrrole in a single form, in the present invention, polypyrrole in different forms (granular and dendritic) is uniformly dispersed and fixed on the surface of a cubic Prussian blue framework with an inner concave step structure by means of attachment growth and series connection, wherein the dendritic polypyrrole can connect each independent structure in series to increase the overall conductivity, and the granular polypyrrole can be attached to the surface of the material to effectively improve the conductivity and specific surface area of ​​the material. Therefore, the Prussian blue step cubic framework / polypyrrole composite electrode material of the present invention, under the joint action of the cubic Prussian blue framework with an inner concave step structure and polypyrrole, can form a multidimensional structure by means of attachment growth, series connection, etc., so that the composite material exhibits very excellent redox activity and conductivity, and has a large electrolyte contact area, a large number of active sites, and Na + It has the advantages of suitable diffusion path, good conductivity and stable structure. When used to prepare capacitive deionization electrodes, it can significantly promote the improvement of the desalination performance of the electrode, has high use value and good application prospects.

[0031] (2) The present invention also provides a method for preparing a Prussian blue stepped cubic framework / polypyrrole composite electrode material, by optimizing the amount of each raw material to ensure that the reaction of each raw material in the system is not sufficient within the reaction time, specifically, when methyl orange and pyrrole are completely reacted, the polypyrrole generated is a dendritic structure, while the pyrrole that is not reacted with methyl orange is a granular polypyrrole, so that polypyrroles of different forms (granular and dendritic) are in situ attached to the surface of a cubic Prussian blue framework with an inner concave stepped structure under ice bath conditions to form a large electrolyte contact area, a large number of active sites, and a Na + Prussian blue stepped cubic framework / polypyrrole composite electrode material with suitable diffusion path, good conductivity and stable structure.

[0032] (3) The present invention also provides a capacitor deionization electrode, which is prepared from a Prussian blue step cubic framework / polypyrrole composite electrode material and has a faster ion diffusion rate, a larger specific capacitance, better cycle stability, a higher charging efficiency, and a lower energy consumption. At the same time, when the capacitor deionization electrode is used for solution desalination, it has a higher desalination rate and a better desalination effect.

[0033] Compared with the prior art, the advantages of the present invention are:

[0034] (1) Innovative combination of new electrode materials: By organically combining Prussian blue analogs (PBAs) with polypyrrole (PPy), not only the conductivity of the material is enhanced, but also the redox activity of PBAs is utilized to achieve efficient adsorption of ions in water. This combination strategy breaks through the performance limitations of traditional CDI electrode materials and provides a new way to improve desalination efficiency.

[0035] (2) Prussian blue cubic step structure design: The cubic Prussian blue framework with an inner concave step structure has crystals with abundant steps and concave surfaces. These features significantly increase the contact area between the electrode and the solution, providing more active sites for ion adsorption, thereby improving the adsorption efficiency. At the same time, the Prussian blue cubic step structure allows more ions to be adsorbed on the electrode surface, thereby improving the overall performance of the CDI system.

[0036] (3) Formation of a multidimensional conductive network: A continuous conductive network is formed by attaching, growing and connecting polypyrroles of different forms in series on the cubic step structure of Prussian blue. This network not only improves the conductivity of the electrode, but also enhances the overall mechanical stability of the electrode material, ensuring the stability of the electrode performance during long-term desalination. At the same time, the formation of this multidimensional conductive network improves the electron transfer efficiency, thereby enhancing the electrochemical performance of the electrode.

[0037] (4) With the characteristics of high adsorption capacity and fast desalination rate, the CDI system can treat a large amount of brine in a short time, improve water treatment efficiency and reduce energy consumption. At the same time, the realization of this high adsorption capacity and fast desalination rate is due to the special structure and chemical properties of the electrode material, which makes the CDI system have obvious advantages in treating high-salinity water bodies.

[0038] (5) Long-term cycle stability: After multiple cycles of use, the electrode material can still maintain good stability, which is crucial for the practical application and commercialization of CDI technology and ensures the reliability and durability of the system. The realization of long-term cycle stability means that the electrode material can undergo multiple adsorption and desorption processes without losing performance, which is crucial for reducing operating costs and improving system economy.

[0039] (6) High efficiency desalination performance: In the present invention, the CDI system has shown excellent desalination performance in the experiment, especially when treating high-salinity water. This high efficiency desalination capability makes the present invention have a wide range of application prospects in the fields of seawater desalination and brackish water treatment. At the same time, the realization of high efficiency desalination performance provides a new technical approach to solving the global freshwater resource shortage problem.

[0040] (7) Application potential and cost-effectiveness: The design of the new electrode material is not only innovative in theory, but also shows significant commercial potential in practical applications. Its low cost and high efficiency make CDI technology more economical and affordable, which helps promote the development of environmentally friendly and sustainable water treatment technology. The combination of application potential and cost-effectiveness makes the present invention not only technologically advanced but also economically feasible, providing a solid foundation for future commercialization and large-scale production.

[0041] (8) Environmental friendliness: In the present invention, the environmental impact is fully considered during the design, and the materials and preparation methods used meet the environmental protection requirements, ensuring the environmental friendliness of the water treatment process. Based on the consideration of environmental friendliness, the present invention not only meets the water treatment needs, but also meets the requirements of sustainable development, which helps to reduce the negative impact on the environment.

[0042] (9) Easy to scale up production: In the present invention, the material preparation method is scalable and easy to achieve large-scale production, which is crucial for reducing costs and promoting application. At the same time, it has the characteristics of being easy to scale up production, which means that the present invention can be quickly transformed from laboratory research to practical application, meeting the market demand for efficient water treatment technology.

[0043] Therefore, in the present invention, through innovative material design and structural optimization, an efficient, stable and environmentally friendly CDI technology is provided, which is expected to bring revolutionary changes in the field of water treatment. At the same time, with further research and development, the present invention is expected to play a greater role in the future water treatment and energy recovery fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0045] Figure 1 Raman images of the Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2) prepared in Example 1 of the present invention, the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy).

[0046] Figure 2 SEM images of the Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2) prepared in Example 1 of the present invention, the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy).

[0047] Figure 3 TEM images of the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-1) prepared in Example 1 of the present invention, the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy).

[0048] Figure 4 The pore size distribution diagrams are of the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-1) prepared in Example 1 of the present invention, the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy).

[0049] Figure 5 This is a cyclic voltammogram of the capacitive deionization electrode made of Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), a cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) in Example 2 of the present invention.

[0050] Figure 6The cyclic voltammetry curves of the capacitive deionization electrode made of the Prussian blue step cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-1) at different scanning speeds in Example 2 of the present invention are shown.

[0051] Figure 7 This is a constant current charge and discharge diagram of the capacitive deionization electrode made of Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), a cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) in Example 2 of the present invention.

[0052] Figure 8 This is a graph showing the change in specific capacitance-current density of the capacitive deionization electrode made of the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) in Example 2 of the present invention.

[0053] Fig. 9 This is the electrochemical impedance diagram of the capacitive deionization electrode made of Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), a cubic Prussian blue framework with an inner concave step structure (FeHCFe), and polypyrrole (PPy) in Example 2 of the present invention.

[0054] Fig.10 Schematic diagram of the structure of the capacitive deionization device in Example 3 of the present invention.

[0055] Fig.11 This is a graph of the conductivity-time variation corresponding to the desalination of a saline solution by a capacitive deionization device constructed of Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), a cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) in Example 3 of the present invention.

[0056] Fig.12This is a graph showing the unit desalination amount-time variation curve corresponding to the desalination of a saline solution by a capacitive deionization device constructed of a Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), a cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) in Example 3 of the present invention.

[0057] Fig.13 This is a graph showing the change in unit desalination rate - unit desalination amount when a capacitive deionization device constructed of Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), a cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) in Example 3 of the present invention desalinates a saline solution.

[0058] Fig.14 This is a diagram showing the corresponding cyclic electrosorption effect when a capacitive deionization device constructed by a Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-1) in Example 3 of the present invention desalinates a saline solution. DETAILED DESCRIPTION

[0059] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.

[0060] Example 1

[0061] A Prussian blue stepped cubic framework / polypyrrole composite electrode material comprises a cubic Prussian blue framework with an inner concave stepped structure and polypyrrole, wherein the polypyrrole comprises granular polypyrrole and dendritic polypyrrole, wherein the granular polypyrrole is attached and grown on the surface of the Prussian blue cubic framework and the surface of the dendritic polypyrrole, and the dendritic polypyrrole is connected between the cubic Prussian blue frameworks to form a series network structure.

[0062] In this embodiment, the mass ratio of the cubic Prussian blue framework to the polypyrrole is 1:1.

[0063] A method for preparing the Prussian blue step cubic framework / polypyrrole composite electrode material in the present embodiment comprises the following steps:

[0064] (1) Preparation of a cubic Prussian blue framework with an inner concave step structure

[0065] (1.1) Mix 5 mmol of benzoic acid and 20 mL of ethanol to prepare solution A. Mix 1.4 mmol of Na4Fe(CN)6·10H2O and 15 mL of water to prepare solution B.

[0066] (1.2) Solution A and solution B were fully mixed and placed in a 45 mL autoclave for hydrothermal (hot solvent reaction) at 120°C for 6 h. The resulting product was then washed and centrifuged with deionized water and ethanol (first washed three times by centrifugation with ethanol, then washed three times by centrifugation with deionized water). Finally, the product was vacuum dried at 60°C overnight (12 h) to obtain a cubic Prussian blue framework with an inner concave step structure, denoted as FeHCFe.

[0067] (2) Preparation of Prussian blue step cubic framework / polypyrrole composite electrode materials

[0068] (2.1) 120 mg of methyl orange (MO) and 120 mg of a cubic Prussian blue framework with an inner concave step structure were mixed with 160 mL of ultrapure water, ultrasonicated for 15 min, stirred at 400 r / min for 12 min, and then 280 μL of pyrrole (Py) was added. The mixture was stirred at 400 r / min for 15 min to prepare solution C. 1.08 g of FeCl3·6H2O was added to 18.4 mL of ultrapure water, stirred at 700 r / min for 15 min, and mixed thoroughly to prepare solution D.

[0069] (2.2) Solution C and solution D were mixed evenly, placed in an ice bath at 0°C, and reacted at 400 r / min for 24 h. After the reaction was completed, the solution was centrifuged at a speed of 6500 r / min, and the single centrifugation time was 5 min to obtain a solid product. Finally, ethanol and deionized water were used for centrifugal washing (first centrifuge and wash with ethanol until the supernatant was clear, and then centrifuge and wash with deionized water three times) until the supernatant was clear. The solid product was then placed in a drying oven at 60°C and dried for 24 h to obtain a Prussian blue step cubic framework / polypyrrole composite electrode material, recorded as FeHCFe / PPy-1.

[0070] In this embodiment, Prussian blue stepped cubic framework / polypyrrole composite electrode materials with different mass ratios of cubic Prussian blue framework and polypyrrole are also prepared. Their preparation methods are basically the same as the preparation method of the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-1), with the only difference being that in step (2.1), the amounts of the cubic Prussian blue framework with an inner concave step structure are 60 mg and 240 mg, respectively, and the corresponding Prussian blue stepped cubic framework / polypyrrole composite electrode materials are named FeHCFe / PPy-0.5 and FeHCFe / PPy-2, respectively.

[0071] In the Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-2) prepared in this embodiment, the mass ratios of polypyrrole and cubic Prussian blue framework are 1:0.5 and 1:2, respectively.

[0072] In this embodiment, polypyrrole (PPy) is also prepared, comprising the following steps:

[0073] (a) 120 mg of methyl orange (MO) was mixed with 160 mL of ultrapure water, ultrasonicated for 15 min, stirred at 400 r / min for 12 min, and then 280 μL of pyrrole (Py) was added and stirred at 400 r / min for 15 min to prepare solution C; 1.08 g of FeCl3·6H2O was added to 18.4 mL of ultrapure water, stirred at 700 r / min for 15 min, and mixed thoroughly to prepare solution D.

[0074] (b) Solution C and solution D were mixed evenly, placed in an ice bath at 0°C, and reacted at 400 r / min for 24 h. After the reaction was completed, the solution was centrifuged at 6500 r / min for 5 min to obtain a solid product. The solid product was washed by centrifugation with ethanol and deionized water (first centrifuged and washed with ethanol until the supernatant was clear, and then centrifuged and washed with deionized water three times) until the supernatant was clear. The solid product was placed in a drying oven at 60°C and dried for 24 h to obtain polypyrrole, denoted as PPy.

[0075] Figure 1 The Raman images are of the Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2) prepared in Example 1 of the present invention, the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy). Figure 1 The Raman spectra of FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2, PPy and pure FeHCFe can determine the 1380 cm -1 (D belt) and 1550cm -1 The two carbon matrix peaks near (G band) are introduced by PPy. After increasing the proportion of FeHCFe in the material, the I D / I G The values ​​of I D / I GThe values ​​are 1.582, 1.67, 1.81, and 2.25, respectively. After PPy is compounded with FeHCFe, more defects may be generated in the material and the disorder of the structure will increase. The D peak intensity of FeHCFe / PPy-0.5, FeHCFe / PPy-1, and FeHCFe / PPy-2 is greater than the G peak intensity, and their degree of graphitization may be lower. Compared with the D peak of PPy (1392cm -1 ), the D peaks of FeHCFe / PPy-0.5, FeHCFe / PPy-1, and FeHCFe / PPy-2 have a slight red shift (1381 cm -1 ), which may be caused by the change of the original molecular bonds of PPy after it is compounded with FeHCFe.

[0076] Figure 2 The SEM images of the Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) prepared in Example 1 of the present invention are shown in FIG. Figure 2 It can be seen that the pure PPy material presents the characteristics of a mixture of dendritic structure and particle structure. The diameter of the dendritic structure is between 300nm and 1μm, and the diameter of the particle structure is about 100nm. The particle structure is attached to the dendritic structure, and the dendritic structure is connected in series through interweaving and overlapping. This structure provides a large number of attachment sites and migration channels. Figure 2 It is known that pure FeHCFe presents a cubic structure with a concave step structure on the surface of the cube, which is formed by formic acid etching sodium ion hexacyanoferrate, which effectively increases the surface area of ​​the material and enriches the attachment sites. Figure 2 This is fully reflected in the fact that a large number of PPy particle structures are attached to the concave step structure, which effectively improves the conductivity of the cubic structure and further increases the surface area of ​​the cube. Figure 2 The structural characteristics of the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-1) show that the structure consists of three parts: a dendritic structure, a particle structure, and a cubic structure with concave steps. The three structures are fully combined through attachment, stacking, and interweaving. The particle structure is attached to the dendritic structure and the cubic structure with concave steps, while the dendritic structure connects the relatively scattered structures to form a multi-dimensional structure. Figure 2It can be found in the FeHCFe / PPy-0.5 and FeHCFe / PPy-2 that the FeHCFe / PPy-2 has significantly fewer particle structures attached to the cubic structure with concave steps than FeHCFe / PPy-1, which may lead to insufficient utilization of the attachment sites on the surface of the cube and relatively lower conductivity improvement; while in the image of FeHCFe / PPy-0.5, it can be found that there are excessive particle structures attached to the surface of the cube, which may block the migration channels on the surface of the structure and cause a decrease in migration efficiency. By comparison, it can be seen that FeHCFe / PPy-1 has a better balance between conductivity and migration efficiency (including ion and electron transport) than the other two composite materials, achieving the most suitable balance point, thus having higher efficiency.

[0077] Figure 3 TEM images of the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-1), the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) prepared in Example 1 of the present invention. Figure 3 High-resolution TEM (HRTEM) showed that the lattice spacing of FeHCFe / PPy-1 was 0.505 nm, indicating the tandem structure and multi-dimensional configuration of the composite material.

[0078] Figure 4 The pore size distribution diagrams of the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-1), the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) prepared in Example 1 of the present invention are shown in FIG. Figure 4 The N2 adsorption-desorption isotherms of the relevant materials are shown in the figure for further investigation of the specific surface area (SSA) and pore volume of the samples. Pure PPy has the largest SSA (32.46 m 2 g -1 ), compared with PPy, the SSA of pure FeHCFe is only 2.25m 2 g -1 This is because PPy has more micro-nano structures in its structural composition. Among all the synthesized materials, SSA increases with the increase of the proportion of PPy (Table 1). Figure 4 As shown, the N2 adsorption-desorption isotherm of FeHCFe / PPy-1 material presents a type II isotherm, and the pore size distribution of the material is mainly between 20 and 30 nm.

[0079] In this embodiment, the specific surface area and pore volume data of Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), cubic Prussian blue framework with an inner concave step structure (FeHCFe), and polypyrrole (PPy) were also tested. The results are shown in Table 1.

[0080] Table 1 Comparison of specific surface area and pore volume of different materials

[0081] sample <![CDATA[Specific surface area (m 2 g -1 )]]> <![CDATA[Total pore volume (cm 3 g -1 )]]> FeHCFe 2.2464 0.0081 PPy 32.4636 0.11558 FeHCFe / PPy-0.5 28.7635 0.11016 FeHCFe / PPy-1 24.2164 0.10283 FeHCFe / PPy-2 21.7924 0.096446

[0082] The specific surface area (SSA) and pore size distribution of the samples were further investigated using N2 adsorption-desorption isotherms. Among the tested materials, pure polypyrrole (PPy) has the largest specific surface area, reaching 32.46 m2 g -1 , while the specific surface area of ​​pure FeHCFe is significantly lower, only 2.25 m2 g -1 The reason for this difference is that the PPy component contains more micro- and nanostructures. The increase in PPy content is beneficial to increase the specific surface area and pore volume of the composite material, which helps to improve the adsorption performance of the material, as shown in Table 1. In general, PPy also plays a role in increasing the specific surface area and pore volume of the composite material, which in turn promotes the Na + adsorption.

[0083] Embodiment 2:

[0084] A capacitor deionization electrode is prepared by using a Prussian blue step cubic framework / polypyrrole composite electrode material, comprising the following steps:

[0085] Weigh 32 mg each of the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2) prepared in Example 1, a cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy), add 4 mg of conductive carbon black and 4 mg of polyvinylidene fluoride (PVDF) and mix evenly, then slowly add N-methylpyrrolidone (NMP) dropwise, stir to form a uniform colloid, apply it on a graphite plate (4 cm×4 cm) with a pestle, and vacuum dry for 12 h to obtain a capacitive deionized electrode.

[0086] The capacitor deionized electrode prepared in this example was cut into 1 cm × 1 cm squares as working electrodes, silver / silver chloride electrodes as reference electrodes, platinum electrodes as counter electrodes, and 1 M NaCl solution as electrolyte. Electrochemical performance tests such as cyclic voltammetry, constant current charge and discharge, and electrochemical impedance spectroscopy were performed using an electrochemical workstation.

[0087] Figure 5 The cyclic voltammetry curves of the capacitive deionization electrodes made of the Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), the cubic Prussian blue framework with an inner concave stepped structure (FeHCFe), and polypyrrole (PPy) in Example 2 of the present invention are shown in FIG. Figure 5 As shown in the figure, when pure PPy is subjected to CV testing, the CV curve is close to a rectangle, which indicates that it is controlled by EDLC, while pure FeHCFe shows obvious redox peaks, and the distance between the peaks is far, which is controlled by Faraday capacitance. Figure 5 As shown, the CV curves of the Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2) composed of two monomers have obvious redox peaks and the characteristics of rectangular curves. It can be seen that the CV curves of the Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2) are affected by the synergistic effect of EDLC and Faraday capacitance.

[0088] Figure 6 The cyclic voltammetry curves of the capacitive deionization electrode made of Prussian blue step cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-1) at different scanning speeds in Example 2 of the present invention are shown in FIG. Figure 6 It can be seen that when the composite material FeHCFe / PPy-1 is subjected to CV tests at different scanning speeds, the corresponding curve characteristics are well retained, which shows that the composite material has good stability.

[0089] Figure 7 The constant current charge-discharge diagram of the capacitive deionization electrode made of the Prussian blue step cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), the cubic Prussian blue framework with an inner concave step structure (FeHCFe), and polypyrrole (PPy) in Example 2 of the present invention. In order to further study the electrochemical properties of the material, a GCD test was performed. Figure 7 As shown in the figure, the GCD curves of pure FeHCFe and the composite materials containing FeHCFe both show a charge-discharge platform, which means that these materials have undergone redox reactions during the test, which is consistent with the results of the CV test, while the GCD curve of PPy does not have a charge-discharge platform.

[0090] Figure 8 The graph is a graph showing the specific capacitance-current density change of the capacitive deionization electrode made of the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) in Example 2 of the present invention. Figure 8 As shown, at 1A g -1 When the current density was tested, the specific capacitance of FeHCFe / PPy-1 reached 152.91 F g -1 , its discharge time reaches 206.7s, the best performance among all materials. -1 At a current density of 1.34 W, the specific capacitance of FeHCFe / PPy-1 is 163.92 F g -1 Compared with pure FeHCFe (121.54F g -1 ) and PPy(157.71F g -1 ) is better, and FeHCFe / PPy-1 has the longest discharge time at various current densities, which means that the specific capacitance of FeHCFe / PPy-1 is the largest, indicating that FeHCFe / PPy-1 has good electrochemical performance. In addition, the single-form PPy prepared by conventional methods has a good electrochemical performance at 0.5A g -1 The specific capacitance at the current density is 30F g -1 .

[0091] Fig. 9 The electrochemical impedance diagram of the capacitive deionization electrode made of the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), the cubic Prussian blue framework with an inner concave stepped structure (FeHCFe), and polypyrrole (PPy) in Example 2 of the present invention. Fig. 9As shown in the figure, EIS tests were performed on various prepared materials. In the high-frequency region of the EIS curve, the curve is close to a circle. The radius of the approximate circle is related to the interface resistance between the electrode surface and the electrolyte body. The larger the radius of the approximate circle, the larger the interface charge transfer resistance; the low-frequency region of the curve is linear, and its slope is related to the ion diffusion rate of the electrode surface. The larger the slope, the stronger the ion diffusion capacity. Pure PPy material has a smaller approximate circle radius in the high-frequency region than FeHCFe material, while FeHCFe has a larger slope in the low-frequency region, and the composite material has a combination of the advantages of both. The ion diffusion capacity of FeHCFe / PPy-0.5 is not as good as that of the other two composite materials, which may be caused by the blockage caused by the large accumulation of PPy on the surface of FeHCFe. The interface charge transfer resistance of FeHCFe / PPy-2 is similar to that of FeHCFe, which may be caused by the insufficient occupation of PPy particles in FeHCFe. While FeHCFe / PPy-1 shows the largest slope in the low-frequency region, the approximate circle radius in the high-frequency region is also relatively small, which means that the structure of this composite material is the most reasonable.

[0092] Embodiment 3:

[0093] An application of a capacitive deionization electrode in solution desalination, specifically: application of a capacitive deionization electrode in desalination of brackish water, comprising the following steps:

[0094] (1) Weigh 32 mg each of the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2) prepared in Example 1, the cubic Prussian blue framework with an inner concave stepped structure (FeHCFe), and polypyrrole (PPy), add 4 mg of conductive carbon black and 4 mg of polyvinylidene fluoride (PVDF), grind evenly, then slowly add N-methylpyrrolidone (NMP) dropwise, stir to form a uniform colloid, apply it on a graphite plate (4 cm×4 cm), and vacuum dry for 12 h to obtain a capacitive deionized electrode.

[0095] (2) Assembling a capacitive deionization device using the capacitive deionization electrode obtained in step (1) as a cathode and an activated carbon electrode as an anode.

[0096] In this step, the preparation method of the activated carbon anode electrode is basically the same as the preparation method of the capacitor deionization electrode, the only difference being that the Prussian blue step cubic framework / polypyrrole composite electrode material is replaced by activated carbon.

[0097] In this step, the structure of the capacitive deionization device is as follows: Fig.10As shown, it includes an activated carbon anode and a capacitor deionization electrode cathode. Specifically: the capacitor deionization device includes an acrylic plate, a silicone gasket, an activated carbon anode, an anion exchange membrane, a silicone gasket, a diaphragm, a cation exchange membrane, a capacitor deionization electrode cathode, a silicone gasket, and an acrylic plate stacked in sequence along the water inlet direction, wherein the activated carbon anode and the capacitor deionization electrode cathode are connected to a DC power supply.

[0098] (3) using the capacitive deionization device in step (2) to perform a desalination experiment on the saline solution, specifically: using 50 mL of a NaCl solution with an initial conductivity of 1000 μs / cm as the saline solution (the concentration of NaCl in the solution is 500 mg / L), desalination treatment is performed under the conditions of an inlet flow rate of 15 mL / min and an applied voltage of 1.5 V to complete the desalination of the saline solution.

[0099] Fig.11 The conductivity-time curve of the capacitive deionization device constructed by the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) in Example 3 of the present invention when desalting a saline solution. Fig.11 As shown in the figure, the conductivity decrease rate of electrodes of different materials after voltage application is significantly different, but the decrease trend is consistent, that is, the decrease rate is fast within ten minutes after voltage application, and tends to be slow after ten minutes. This may be due to the gradual saturation of the adsorption sites of ions. In the desalination test, the time for different materials to reach desalination stability is 20 minutes, which is faster than other materials in the HCDI field. When the electrode made of pure FeHCFe as the active material is subjected to desalination test, the adsorption equilibrium is reached at 20 minutes, and the unit salt adsorption capacity (SAC) at this time is 12.21 mg g -1 In contrast, when the electrode made of PPy as the active material was tested for desalination, the adsorption equilibrium was also reached in 20 min, and the SAC was 18.51 mg g -1 The possible reason is that although pure FeHCFe has sodium storage capacity, its conductivity is poor, while PPy has better conductivity but cannot provide enough adsorption sites, which leads to the poor adsorption performance of both. The composite material of FeHCFe and PPy shows significant synergistic effect.

[0100] Fig.12The graph of unit desalination amount-time variation of the capacitive deionization device constructed by the Prussian blue stepped cubic framework / polypyrrole composite electrode materials (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), the cubic Prussian blue framework with an inner concave stepped structure (FeHCFe), and polypyrrole (PPy) in Example 3 of the present invention for desalination of saline solution. In the desalination test of the three composite materials with different proportions, the SAC of FeHCFe / PPy-1 reached 53.17 mg g -1 Compared with 37.02 mg g of FeHCFe / PPy-0.5 -1 and 40.17 mg g for FeHCFe / PPy-2 -1 There is a significant improvement, which is 4.35 times higher than that of pure FeHCFe and 2.87 times higher than that of pure PPy. This shows that the composite material has a significant synergistic effect compared to the monomer material in the desalination test. The improvement in the performance of the composite material may be due to the complementarity of the two monomers. The composite material has both the sodium storage capacity of FeHCFe and the good electrical conductivity of PPy. The differences in composite materials with different proportions are speculated to be caused by the different degrees of attachment of the PPy particle structure to the FeHCFe cube. The density of the particle structure in the composite material FeHCFe / PPy-0.5 is higher, and these particle structures are excessively attached to the surface of the FeHCFe cube, which may block the FeHCFe cube from adsorbing Na + The channel and the occupation of Na + The adsorption sites of FeHCFe / PPy-2 are reduced, which leads to a decrease in adsorption performance. The composite material FeHCFe / PPy-2 contains fewer PPy structures, which leads to a decrease in the conductivity of the material and thus reduces the desalination performance.

[0101] Fig.13 The graph of the unit desalination rate-unit desalination amount change when the capacitive deionization device constructed by the Prussian blue stepped cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-0.5, FeHCFe / PPy-1, FeHCFe / PPy-2), the cubic Prussian blue framework (FeHCFe) with an inner concave stepped structure, and polypyrrole (PPy) in Example 3 of the present invention desalinates the saline solution. Fig.13 As shown in the figure, FeHCFe / PPy-1 has the highest ion adsorption capacity and ion removal rate, which is located in the upper right corner of the figure. The salt adsorption rate (SAR) of FeHCFe / PPy-1 is as high as 10.25 mg g -1 min -1 Far exceeding the 1.18 mg g of FeHCFe -1 min -1and 1.97 mg g of PPy -1 min -1 , and also has advantages at high SAC values.

[0102] Fig.14 The figure is a graph showing the cyclic electrosorption effect of the capacitive deionization device constructed by the Prussian blue step cubic framework / polypyrrole composite electrode material (FeHCFe / PPy-1) in Example 3 of the present invention when desalting a saline solution. In order to test the cyclic performance of the electrode made of the composite material FeHCFe / PPy-1, a cyclic test was conducted. The test conditions were 1.5 V voltage, 500 mg L NaCl concentration, and 1.5 V. -1 During the test, a total of 14 cycles were performed, with an average SAC of 51.32 mg g -1 The maximum SAC value during the cycle is 53.17 mg g -1 , the minimum value is 48.84 mg g -1 ,like Fig.14 As shown. After the cycle test, it can be determined that the composite material has a certain stability and can ensure the reliability of desalination after multiple cycles.

[0103] In this embodiment, the corresponding electrical adsorption amount when desalting a saline solution using a capacitive deionization electrode prepared using existing Prussian blue and its analogs and polypyrrole electrode materials is compared, and the specific situation is shown in Table 2.

[0104] Table 2 Comparative statistics

[0105]

[0106]

[0107] As shown in Table 2, the Prussian blue step cubic framework / polypyrrole composite electrode material of the present invention exhibits more excellent electrical adsorption performance in capacitive deionization applications, and is higher than the electrical adsorption performance of conventional Prussian blue and its analogs and polypyrrole-based electrode materials under different conditions. It can be seen that the Prussian blue step cubic framework / polypyrrole composite electrode material of the present invention has better performance and higher sodium chloride removal efficiency than similar electrode materials, which can be attributed to: the Prussian blue step cubic framework / polypyrrole composite electrode material has better faradaic capacitance performance and synergistic capacitance effect brought about by the multidimensional structure.

[0108] In summary, the present invention innovatively proposes a Prussian blue step cubic framework / polypyrrole composite electrode material that gives full play to the synergistic effect of composite polypyrrole and Prussian blue step cubic framework. When used as an active material for a capacitor deionization electrode, it is possible to achieve efficient removal of salt in a water body, with very high practical use value and good application prospects. At the same time, the preparation method of the present invention will not sacrifice the inherent properties of the material, can give full play to the advantages of the two, and has the advantages of simple synthesis method, less addition of additional chemical reagents, low economic cost, less energy consumption, short time consumption, and controllable interface structure, suitable for large-scale batch production, and convenient for industrial use. In addition, in the present invention, the capacitor deionization electrode composited by the Prussian blue step cubic framework / polypyrrole composite electrode material, conductive carbon black and a binder has the advantages of large electrolyte contact area, good capacitance performance, high conductivity, good cycle stability, etc., and is a novel electrode with excellent performance. In addition, in the present invention, when the capacitive deionization electrode prepared with the Prussian blue step cubic framework / polypyrrole composite electrode material as raw material is used as the cathode for brackish water desalination, it has the advantages of simple operation, low energy consumption, low cost, excellent desalination performance, good cycle stability, etc., and has good practical application prospects.

[0109] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A Prussian blue step cubic framework / polypyrrole composite electrode material, characterized in that: The invention comprises a cubic Prussian blue framework with an inner concave step structure and polypyrrole, wherein the polypyrrole comprises granular polypyrrole and dendritic polypyrrole; the granular polypyrrole is attached and grown on the surface of the Prussian blue cubic framework and the dendritic polypyrrole, and the dendritic polypyrrole is connected between the cubic Prussian blue framework.

2. The Prussian blue stepped cubic framework / polypyrrole composite electrode material according to claim 1, characterized in that: The mass ratio of the cubic Prussian blue framework to polypyrrole is 0.8-1.5:

1.

3. The Prussian blue step cubic framework / polypyrrole composite electrode material according to claim 1 or 2, characterized in that: The mass ratio of the cubic Prussian blue framework to polypyrrole is 1:

1.

4. A method for preparing a Prussian blue step cubic framework / polypyrrole composite electrode material as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: (1) preparing a cubic Prussian blue framework with an inner concave step structure; (2) mixing the cubic Prussian blue framework with an inner concave step structure obtained in step (1), methyl orange and water, ultrasonicating and stirring to obtain a solution A; the amount of methyl orange used is more than 120 mg; (3) adding pyrrole to the solution A obtained in step (2), stirring, and obtaining a solution B; the amount of pyrrole used is more than 280 μL; (4) adding the solution B obtained in step (3) to the ferric iron salt solution, mixing and reacting in an ice bath, centrifuging, and washing to obtain a Prussian blue step cubic framework / polypyrrole composite electrode material; the amount of the ferric iron salt solution used is above 18.4 mL.

5. The preparation method according to claim 4, characterized in that: In step (1), the method for preparing the cubic Prussian blue framework having an inner concave step structure comprises the following steps: (1.1) Mix benzoic acid and ethanol to prepare solution C; (1.2) Solution C and solution D are mixed to perform a hot solvent reaction, centrifuged, washed, and dried to obtain a cubic Prussian blue framework with an inner concave step structure; the solution D is prepared by mixing Na4Fe(CN)6·10H2O with water.

6. The preparation method according to claim 5, characterized in that: In step (1.1), the ratio of benzoic acid to ethanol is 1 mmoL: 4 mL; In step (1.2), the volume ratio of solution C to solution D is 4:3; the ratio of Na4Fe(CN)6·10H2O to water is 1.4mmoL:15mL; the hot solvent reaction is carried out at a temperature of 120°C; the hot solvent reaction time is 6h; the centrifugal speed is 6500r / min; the washing is to wash the centrifuged product with ethanol and deionized water in sequence; the number of washings is 3 times; the drying is carried out under vacuum conditions; the drying temperature is 60°C; and the drying time is 12h.

7. The preparation method according to any one of claims 4 to 6, characterized in that In step (2), the mass ratio of the cubic Prussian blue framework to methyl orange is 1:1; the ratio of methyl orange to water is 3 mg:4 mL; the ultrasonic time is 15 min; the stirring is carried out at a rotation speed of 400 r / min; and the stirring time is 12 min; In step (3), the volume ratio of pyrrole to solution A is 0.7:40; the stirring is performed at a rotation speed of 400 r / min; and the stirring time is 15 min; In step (4), the ferric iron salt solution is a ferric chloride solution; the ferric chloride solution is prepared by the following method: adding FeCl3·6H2O to ultrapure water, stirring for 15 minutes at a rotation speed of 600r / min to 800r / min, to obtain a ferric chloride solution; the ratio of FeCl3·6H2O to ultrapure water is 1.08g:18.4mL; the reaction temperature is 0°C; the reaction time is 24h; the reaction is carried out at a rotation speed of 600r / min to 800r / min; the centrifugal speed is 6500r / min; the single centrifugal time is 5min; The washing step is to use ethanol and deionized water to wash the centrifuged product in sequence; the washing step is performed 3 times; the drying temperature is 60° C.; and the drying time is 24 hours.

8. A capacitive deionization electrode, characterized in that: The capacitive deionization electrode is prepared from the Prussian blue step cubic framework / polypyrrole composite electrode material according to any one of claims 1 to 3 or the Prussian blue step cubic framework / polypyrrole composite electrode material prepared by the preparation method according to any one of claims 4 to 7.

9. The capacitive deionization electrode according to claim 8, characterized in that: The capacitor deionization electrode is prepared from a Prussian blue step cubic framework / polypyrrole composite electrode material, conductive carbon black and a binder, and comprises the following steps: mixing the Prussian blue step cubic framework / polypyrrole composite electrode material, conductive carbon black and a binder, adding a solvent to form a colloid; coating the colloid on a conductive carrier, and drying to obtain a capacitor deionization electrode; the mass ratio of the Prussian blue step cubic framework / polypyrrole composite electrode material, conductive carbon black and binder is 8-9:0.8-1:0.8-1; the binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol and polypropylene; and the solvent is N-methylpyrrolidone.

10. Use of the capacitive deionization electrode as claimed in claim 8 or 9 in solution desalination.

Citation Information

Patent Citations

  • Modified prussian blue material, sodium ion battery positive electrode plate and preparation method

    CN106960956A

  • Preparation method of metal-organic framework / polypyrrole hybrid conductive electrode

    CN110117049A

  • Stabilization of battery electrodes using polymer coatings

    US20140127592A1

  • Prussian blue analogue NANO positive electrode material, preparation method therefor and sodium ion battery

    WO2024168546A1